2011
DOI: 10.1038/hr.2011.196
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced cardiomyocyte hypertrophy in vitro is TAK1-dependent and Smad2/3-independent

Abstract: Cardiac hypertrophy occurs as an adaptation to hypertension but a sustained hypertrophic response can ultimately lead to heart failure. Angiotensin-II (Ang II) is released following hemodynamic overload and stimulates a cardiac hypertrophic response. AngII also increases expression of the regulatory cytokine, transforming growth factor-b1 (TGFb1), which is also implicated in the cardiac hypertrophic response and can stimulate activation of Smad2/3 as well as TGFb-activated kinase 1 (TAK1) signaling mediators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 27 publications
4
39
0
1
Order By: Relevance
“…Smad2 activation was induced by AngII in isolated CFs, as we demonstrated in Figure 7(A) and in our previous study [29]. AngII-induced myocyte hypertrophy is not only exclusively dependent upon endogenous TGF- β but also is TAK1-dependent and Smad2/3-independent in vitro [45]. Matsumoto-Ida et al [46] showed that TAK1 protein is exclusively localized in myocytes in the non-infarct zone after experimental MI and thus postulated that the activation of the TGF- β 1/TAK1/p38 MAPK pathway in myocyte is involved in ventricular remodelling.…”
Section: Discussionsupporting
confidence: 79%
“…Smad2 activation was induced by AngII in isolated CFs, as we demonstrated in Figure 7(A) and in our previous study [29]. AngII-induced myocyte hypertrophy is not only exclusively dependent upon endogenous TGF- β but also is TAK1-dependent and Smad2/3-independent in vitro [45]. Matsumoto-Ida et al [46] showed that TAK1 protein is exclusively localized in myocytes in the non-infarct zone after experimental MI and thus postulated that the activation of the TGF- β 1/TAK1/p38 MAPK pathway in myocyte is involved in ventricular remodelling.…”
Section: Discussionsupporting
confidence: 79%
“…41 Activation of TAK1 was well-documented to pivotally induce cardiac hypertrophic growth at baseline or in response to pressure overload, [41][42][43][44] whereas a recent study reported that cardiacspecific depletion of TAK1 induced cell death and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 is a member of the MEKK family central to many critical physiological processes 40 and is designated as a pivotal strategic point involved in the development of cardiac hypertrophy. 41 Activation of TAK1 was well-documented to pivotally induce cardiac hypertrophic growth at baseline or in response to pressure overload, [41][42][43][44] whereas a recent study reported that cardiacspecific depletion of TAK1 induced cell death and cardiac dysfunction. 45 Such discrepancy may be reconciled by the dual role of TAK1 in the regulation of myocyte survival and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The Ang II growth effects, proliferation versus hypertrophy, are dependent on cell type and cell-cycle regulated genes. For example, Ang II exerts hypertrophic effect on cardiomyocytes via TGF β 1 mediated signaling, and blockade of TGF β 1 receptor abrogates Ang II-mediated cardiomyocytes hypertrophy [125]. In myocardial infarction model (MI), ARB, telmisartan, inhibits cardiac remodeling by reducing cardiomyocytes hypertrophy and fibrosis via an anti-inflammatory effect and activation of peroxisome proliferators-activated receptor gamma (PPAR γ ) [126].…”
Section: Raas and Vascular Remodelingmentioning
confidence: 99%